TUBERKULOSIS RENAL PADA ANAK - RT Damanik, Irene (Jurnal Kedokteran Methodist, 2022)
Objectives : Renal TB accounts for 14–41% of all cases of pulmonary TBC in developed countries, that usually occurs 5–15 years after primary pulmonary infection with complication in 3–4%. Non-specific constitutional and insidious onset and symptoms lead to delayed diagnosis also rapid progression to a non-functioning kidney. Clinical Features : A-5-year-old, boy man was admitted to our institution due to dysuria, and flank pain. He had history with OAT therapy has been followed for 1 year and fever for 3 days. He had complaint of cough and night sweat. He had past medical history of lung tuberculosis. Intervention and outcomes : This patient had pulmonary X-ray with suggested primary TB with left hillar lymphadenopathy. Abdominal ultrasound showed hypoechoic cortical nodul in tha right kidney, suggestive pyelonephritis and bilateral hydronephrosis. Intravenous pyelography (IVP) examination demonstrated bilateral hydronephrosis, irregular cortex and upper-lower calyx stenosis with cortical scarring. Urinary examination revealed leucocyturia, negative for bacteria, nitrite and cast. Conclusion:. Renal TB is the second most common from of extra-pulmonary TB after lymph node TB. Patients with genitourinary tuberculosis usually have local symptoms including frequent urination and dysuria. Renal calcification is a common manifestation of tuberculosis on conventional radiographs, occurring in 24%-44% of patients. Extensive parenchymal calcification of the non-functioning kidney and autonephrectomy (putty renal) is characteristic of end-stage tuberculosis.